2016
DOI: 10.1017/s0950268816000960
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA against sporozoite-specific embryogenesis-related protein (TgERP) in the study of horizontally transmitted toxoplasmosis via T. gondii oocysts in endemic settings

Abstract: The aim of this study was to contribute to the better understanding of the relative epidemiological importance of different modes of infection with respect to horizontal transmission of Toxoplasma gondii in endemic settings. We investigated the prevalence of salivary IgA against a sporozoite-specific embryogenesis-related protein (TgERP) in a highly endemic area for toxoplasmosis in Brazil in order to pinpoint parasite transmission via oocysts. Prevalence calculated by salivary IgA specific to TgERP was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Wild foxes often have high seroprevalences of T. gondii with for example, 35% seroprevalence found in populations in Austria (52) and 100% in Czech Republic (53). This is consistent with high levels of exposure to the parasite often seen in human populations: for example in Brazil, human population seroprevalence can reach up to 80-90% (54,55), in France 89% (56) and in Northern Ireland 85% (57). Wild foxes also have longer lifespans relative to the commonly studied rodent animal models, allowing time for the accumulation of by-product effects of neurotropic infection that are seen in humans.…”
Section: Introductionmentioning
confidence: 66%
“…Wild foxes often have high seroprevalences of T. gondii with for example, 35% seroprevalence found in populations in Austria (52) and 100% in Czech Republic (53). This is consistent with high levels of exposure to the parasite often seen in human populations: for example in Brazil, human population seroprevalence can reach up to 80-90% (54,55), in France 89% (56) and in Northern Ireland 85% (57). Wild foxes also have longer lifespans relative to the commonly studied rodent animal models, allowing time for the accumulation of by-product effects of neurotropic infection that are seen in humans.…”
Section: Introductionmentioning
confidence: 66%
“…While in domestic cats, oocyst shedding occurs for only 1-3 weeks after initial infection, in wild feline species shedding may potentially continue intermittently for life [3]. Ingestion of these sporulated oocysts, which contaminate crops, soil, and water sources [4,5], or consumption of bradyzoites from raw or undercooked meat comprise the two major horizontal routes of transmission. Indeed, these parasite stages are responsible for a substantial burden of postnatally acquired infections, causing both sporadic outbreaks of acute, symptomatic disease in immunocompetent adults [6] and severe toxoplasmosis in immunocompromised individuals including HIV/AIDS patients (following reactivation of bradyzoites into disseminating tachyzoites) [7].…”
mentioning
confidence: 99%
“…The authors suggested ERP to be an early infection marker (despite its recognition by chronically infected humans) due to a unique exposure of the immune system to sporozoites vs. a permanent exposure to tachyzoite or bradyzoite stages. In further studies higher detection rates of ERP by human sera derived from settings with possibly high environmental oocysts contamination were described [50,75], compared to sera from areas where infection by the meat route was considered predominant [74]. Vieira et al reported the detection of anti-ERP antibodies in chickens and a high prevalence of anti-ERP antibodies in humans, providing evidence for the relevance of environmental oocysts contamination due to underground water contamination [50].…”
Section: Sporozoite Proteinsmentioning
confidence: 99%
“…Over the last decade, three distinct proteins specifically expressed by T. gondii sporozoites, namely ERP, SporoSAG and CCp5A, have been reported to be able to detect oocystdriven infections by serological tests (Tables 2 and 3). The ERP protein, which was employed in several seroepidemiological studies [50,62,74,75], is part of a group of four molecules annotated as 'late embryogenesis abundant domaincontaining proteins' (LEAs). They are potentially involved in conferring stress resistance to the oocyst [77,78], and the encoding genes are significantly upregulated in this parasite stage.…”
Section: Sporozoite Proteinsmentioning
confidence: 99%